Conversation analysis in the classroom interaction: A literature review - Tiara Nove Ria; Desi Surlitasari Dewi; Eka Wilany (Universitas Pandanaran, 2022)
This article presents the outcomes of empirical investigations employing Conversation Analysis (CA) to analyse classroom interaction, which is based on a review of 20 academic papers. In this review, we describe (1) Conversational analysis in classroom interactions, (2) Classroom interaction problems discovered through conversational analysis, and (3) Pedagogical implications of conversational analysis in teacher training through reflective practice. Findings show that by analyzing the studies of conversation analysis in classroom interaction, the researchers tried to figure out the pattern of interaction in several aspects such as verbal and nonverbal interaction, turn-taking, repair management, and adjacency pairs. They also used conversation analysis to look at a problem that happened in classroom interaction. In addition, conversation analysis is used in a reflective practice with pedagogical consequences in teacher education. This review adds to our understanding of CA while also providing important information for those who want to use it to better understanding of classroom interaction.Keywords: conversation analysis, classroom interaction, reflective.